In-building heat recovery mitigates adverse temperature effects on biological wastewater treatment: A network-scale analysis of thermal-hydraulics in sewers. (1st October 2021) - Hadengue, Bruno; Joshi, Prabhat; Figueroa, Alejandro; Larsen, Tove A.; Blumensaat, Frank
Highlights: We predict the evolution of wastewater heat budgets from the tap to the WRRF inflow. Lateral connections cannot be ignored in system-wide thermal-hydraulic analyzes. Shower drain heat recovery lowers the inflow temperature at the WRRF only marginally. Lateral connections and secondary sewer lines are major thermal dampers . Abstract: Heat recovery from wastewater is a robust and straightforward strategy to reduce water-related energy consumption. Its implementation, though, requires a careful assessment of its impacts across the entire wastewater system as adverse effects on the water and resource recovery facility and competition among heat recovery strategies may arise. A model-based assessment of heat recovery from wastewater therefore implies extending the modeling spatial scope, with the aim of enabling thermal-hydraulic simulations from the household tap along its entire flow path down to the wastewater resource recovery facility. With this aim in mind, we propose a new modeling framework interfacing thermal-hydraulic simulations of (i) households, (ii) private lateral connections, and (iii) the main public sewer network. Applying this framework to analyze the fate of wastewater heat budgets in a Swiss catchment, we find that heat losses in lateral connections are large and cannot be overlooked in any thermal-hydraulic analysis, due to the high-temperature, low-flow wastewater characteristics maximizing heat losses to the environment. Further, we find that implementing shower drain heat recovery devices in 50% of the catchment's households lower the wastewater temperature at the recovery facility significantly less – only 0.3 K – than centralized in-sewer heat recovery, due to a significant thermal damping effect induced by lateral connections and secondary sewer lines. In-building technologies are thus less likely to adversely affect biological wastewater treatment processes. The proposed open-source modeling framework can be applied to any other catchment. We thereby hope to enable more efficient heat recovery strategies, maximizing energy harvesting while minimising impacts on biological wastewater treatment.